Farmer field schools as interventions to reduce the need for antimicrobials in agrifood systems: a longitudinal analysis of layer farmer field school graduates and non-graduates in Kenya - Mark A Caudell; Stella Kiambi; Tabitha Kimani; Anica Buckel; Ruth Omani; Junxia Song; Markus Lipp; Emmanuel Kabali (Antimicrobial Resistance and Infection Control)
Abstract Background Addressing antimicrobial resistance in agri-food systems requires both AMR-specific interventions, which target factors directly impacting AMR (e.g., prescription regulations) and AMR-sensitive interventions, which target factors indirectly impacting AMR transmission (e.g. biosecurity). An approach that can incorporate both AMR-sensitive and AMR-specific interventions is the Farmer Field School approach (FFS), where farmers meet on a demonstration farm to engage/experiment with best production practices across a production cycle. Here, we assess the impacts FFS on AMR-specific and AMR-sensitive practices through evaluating graduates of layer poultry FFSs held in Kenya between 2020 and 2021, alongside a random sample of non-FFS farmers. Methods This longitudinal cross-sectional study was conducted in Kiambu County, Kenya. The farms of 56 FFS graduates and 24 randomly selected non-FFS farmers were visited monthly across an eight-month period in 2022 (N = 610 visits). Data was collected on production costs, biosecurity practices, indicators of flock health, and interactions with the professional veterinary sector. Multiple regression models clustering at the farm level were used to evaluate the impacts of FFS participation. Results Across the eight-month evaluation period, FFS graduates were 5.32 times more likely (95% CI: 1.80–15.75) than non-FFS participants to seek out animal healthcare professionals, 2.60 times more likely (95% CI: 1.11–6.09) to obtain prescriptions, and spent around 7.95 USD (-15.79 - -0.10) less on antimicrobials. FFS participants were four times more likely (95% CI: 1.89–8.47) than non-participants to keep clean drinkers and feeders and 2.5 times more likely (95% CI: 1.08–5.78) to report regularly wearing PPE. Indicators of flock health and costs invested in biosecurity products were not significantly different between FFS participants and non-participants. Conclusions Given the role of animal health professionals, prudent antimicrobial use and improved biosecurity in addressing AMR, the FFS approach should be considered a promising approach to mitigate AMR in agri-food systems. Clinical trial number Not applicable.